Attitudes of European psychiatrists on psychedelics: a qualitative study - Žuljević, Marija Franka; Breški, Nando; Kaliterna, Mariano; Hren, Darko (Frontiers in Psychiatry, 2024)
It is important to understand how mental health practitioners view recent findings on psychedelic-assisted psychotherapy (PAP) as there is potential this treatment may be incorporated into clinical practice. The aim of our study was to explore how psychiatrists who are not involved in psychedelic research and who are located in the European region perceive psychedelics and PAP.We conducted online semi-structured interviews with 12 psychiatry specialists and psychiatry trainees from 8 European countries. Data were analyzed using a general inductive approach informed by codebook thematic analysis.Results: Based on the interviews, we developed four main themes and 14 sub-themes, including (1) Psychedelics hold potential, (2) Psychedelics are dangerous, (3) Future of psychedelics is uncertain, and (4) Psychiatry is ambivalent towards psychedelics.Discussion: Our respondents-psychiatrists acknowledged the potential of PAP but remained cautious and did not yet perceive its evidence base as robust enough. Education on psychedelics is lacking in medical and psychiatric training and should be improved to facilitate the involvement of mental health experts in decision-making on PAP.